Social information use and social learning in non-grouping fishes. (11th September 2017) - Webster, Mike M; Laland, Kevin N
Abstract : We show that some non-shoaling fish species are just as good at copying the food patch choices of other fish as shoaling species. This suggests that living in groups is not a prerequisite for effective social learning. We argue that many solitary species will nevertheless be regularly exposed to social stimuli and can benefit, for example, by obtaining information about where to forage, by copying others. Abstract: Although it is natural to expect that group-living animals will utilize social learning, the expectation for non-grouping species is less clear. Only a few studies have explored the relationship between sociality and social learning. Here we presented 4 non-grouping fish species, fifteenspine sticklebacks ( Spinachia spinachia ), bullhead sculpins ( Cottus gobio ), stone loach ( Barbatula barbatula ) and juvenile European flounders ( Platichthys flesus ) with social information provided by groups of a shoal-forming heterospecific, the threespine stickleback ( Gasterosteus aculeatus ). Using a binary choice procedure we allowed individual test subjects to select between simulated prey patches. Although the test subjects could not sample the patches directly they were able to use information generated by the heterospecific demonstrators to select the "richer" of the 2 patches. For comparison we also recorded social information use in 2 shoaling species, threespine, and ninespine sticklebacks ( Pungitius pungitius ). We saw evidence of social information use and social learning in all 6 species, with no differences seen between social and non-grouping species. We argue that social learning is not likely to be restricted to group-living species, since many solitary species too are regularly exposed to social stimuli from both conspecifics and heterospecifics, and can benefit from using social information. We suggest that researchers have much to learn about the sensory, perceptive, and cognitive mechanisms underlying social learning, and the extent to which these vary (if at all) between grouping and non-grouping species.